The Microsructure and Properties of Aluminium Composite Reinforced with 65 μm Alumina Particles via Powder Metallurgy - Khairel Rafezi Ahmad; Wong Jing Lee; Ruhiyuddin Mohd Zaki; Mazlee Mohd Noor; Mohd Fitri Mohamad Wahid; Shaiful Rizam Shamsudin; Shamsul Baharin Jamaludin, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.